Right anterior minithoracotomy with preservation of the vascular bundle for correction of congenital ventricular septal defects - Kuramys, Serzhan; Bolatbekov, Berik; Joshibayev, Seythan; Yessenbekov, Berikbai; Yessenbekov, Berikbai (Bangladesh Journal of Medical Science, 2024)
Introduction Congenital VSDs require early correction to avoid serious complications. For many years, the gold standard was the median longitudinal sternotomy, but given the gross cosmetic effect, miniapproaches were developed, but right anterior mini-thoracotomies gained popularity. We modified the method of anterior right-sided minithorcatomy by preserving a. et v. mammaria interna and the purpose of the study was to evaluate its effectiveness. Material and Methods The design of the study was prospective with historical control. A total of 82 patients who underwent VSD correction were included in the study. All patients were divided into three groups: group 1 operated by median sternotomy (MS) – 15 patients; Group 2 operated by right anterior minithoracotomy (RAMT) – 38 patients; and the 3rd main group operated on by right antero-lateral thoracotomy (RLMT) with preservation of the artery and vein of the internal mammary artery - 29 patients. Results We revealed the older age in RAMT group. Cardio pulmonary bypasstime and total operation time were shorter in RLMT group, but the time of aortic cross-clamping is shorter than in RAMT group, but longer than in MS group. The length of the skin incision is also the shortest in RLMT group, which enhances the cosmetic effect. Also there were revealed a shorter mechanical lung ventilation time and ICU stay, moreover we observed reduced amount of drainages, as well as quick discharge home. Conclusion Therefore, improved and modificated right antero-lateral minithoracotomy method with preserving a et v mammaria interna is feasible, has a good cosmetic effect, and short hospitalization stay, but should perform with careful preparation of the entire cardiac team. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 514-520